2019
DOI: 10.1111/jocd.13037
|View full text |Cite
|
Sign up to set email alerts
|

A topical regimen improves skin healing and aesthetic outcomes when combined with a radiofrequency microneedling procedure

Abstract: Introduction: Novel topical products formulated using tri-and hexapeptide technology (TriHex Technology ® ; Alastin Skincare ® , Inc) are used to clear the extracellular matrix, stimulate neocollagenesis and elastogenesis, decrease inflammation, and accelerate the epidermal healing process. Aims:This study assessed the efficacy of two topical tri-and hexapeptide-containing products pre-and post-treatment with radiofrequency (RF) microneedling of the photoaged neck with respect to healing and aesthetic outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…24,25 The literature is inconsistent about the use of topical agents and skincare before and after the procedure. [30][31][32][33][34][35][36][37][38][39] Section 3: During the Procedure Before starting the procedure, the skin is free of makeup and should be cleansed with a gentle facial cleanser. 16 Agents such as isopropyl alcohol, chlorhexidine, or hypochlorous acid (HOCl) are frequently used for skin preparation for nonenergy and injectable treatments.…”
Section: Section 1: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 The literature is inconsistent about the use of topical agents and skincare before and after the procedure. [30][31][32][33][34][35][36][37][38][39] Section 3: During the Procedure Before starting the procedure, the skin is free of makeup and should be cleansed with a gentle facial cleanser. 16 Agents such as isopropyl alcohol, chlorhexidine, or hypochlorous acid (HOCl) are frequently used for skin preparation for nonenergy and injectable treatments.…”
Section: Section 1: Preventionmentioning
confidence: 99%
“…24 Common areas most likely to develop edema after treatment are under the eyes and in the neck. 24,30,33,36,50 The edema usually subsides within 3-5 days and regular use of icepacks may help. 24 AEs signs and symptoms may be resolved in a few days or take up to several weeks (Table 3).…”
Section: Section 1: Preventionmentioning
confidence: 99%
“…For example, because abrasion produces slight impairments of the skin barrier, 19 topical formulations used in conjunction with the procedure may reduce irritation and downtime. One previous study demonstrated the safety, tolerability and efficacy of a multi‐ingredient anti‐aging facial moisturizer, 20 when used pre‐ and postmicroneedling; while other investigators have shown that topical tri‐ and hexapeptide‐containing products hasten healing and complement aesthetic outcomes of microneedling 18 . Furthermore, by decreasing the severity and duration of the inflammatory period, the risks of causing a flare‐up of any pre‐existing inflammatory disease (eg, psoriasis, eczema, atopic, or contact dermatitis) may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a specially formulated topical cosmeceutical for use peri‐procedure may increase the safety and tolerability of nonenergy device‐based treatments 18 . Furthermore, additional improvements in multiple efficacy measures may be observed when combining the effects of the nonenergy‐based device treatment, with a topical skincare product.…”
Section: Discussionmentioning
confidence: 99%
“…Several topical regimens have been studied, including a topical tri‐and hexapeptide serum that was applied to the treated region for 2 weeks before and 7 days after RFM treatment. Gold et al 9 concluded that this topical regimen enhanced the RFM device's results. Another study by the same group evaluated an antiaging multi‐ingredient lotion used twice daily for 2 weeks prior and 4 weeks post one RFM treatment in 15 patients.…”
Section: Introduction To Radiofrequency Microneedling (Rfm)mentioning
confidence: 97%